The Effect of Nitrogen Fertilizer Dosage on The Growth and Yield of Balsam (Impatiens balsamina L.) - Riski Nurfadillah; Tri Diana; Helda Valentinadia; Siti Wahyuni (Faculty of Agriculture, Merdeka University Surabaya, Indonesia, 2025)
This study aims to determine the effect of various doses of nitrogen fertilizer on the growth and yield of impatiens (Impatiens balsamina L.). The study was conducted in Bandorasa Village, Cilimus District, Kuningan Regency, using a randomized block design (RBD) with seven treatments of nitrogen fertilizer doses, ranging from 1 g to 4 g of urea per polybag. The parameters observed included root length, plant height, number of leaves, leaf area, net assimilation rate, plant growth rate, chlorophyll content, number of flowers, fresh flower weight, and anthocyanin and carotenoid content. The results showed that nitrogen fertilizer application had a significant effect on several parameters, particularly plant height, number and area of leaves, plant growth rate, and number and weight of flowers. The 2.5 g/polybag dose treatment yielded the best results for most parameters, while excessively high doses tended to reduce growth and flowering efficiency. This study concluded that applying nitrogen fertilizer at the appropriate dose is crucial for optimizing the growth and yield of Impatiens balsamina L.